Persepsi dan Perilaku Wanita Usia Subur dalam Melakukan Tes Inspeksi Visual Asam Asetat - Sahr, Liyasda Amalis; Kusumaningrum, Tanjung Anitasari Indah (Jurnal Promosi Kesehatan Indonesia, 2018)
Background: Sukoharjo Regency is ranked as the four highest positive IVA in Central Java with 19.35% of fertile women have IVA tes positive. This percentage has exceeded the target set by Ministry of health as many as 3%. The lowest of IVA test visits in this Regency was in sukoharjo subdistric which only 47 fertile women (0,19%) has been tested. This research aims to exlplore the perceptions of fertile women in terms of IVA test based on health belief model theory.Method: The research employs qualitative method with case study approach. In-depth interviews were conducted to 14 fertility women and their husbands. One midwife also has been interviewed who was provider of IVA test in Sukoharjo Community Health Centers as an informant triangulation.Results: The results showed that the majority of fertile women has not been tested. The incomprehensive information about IVA test exposure is as the cause of the women didn't want to do the test. Lack of knowledge about the process of IVA test, feel fear and shame including feeling against to religion principles as the inhibitor factors to do test. Beside the need complete socialization from health provider and husband’s support and friend make women easier want to do a IVA test. This study recommends providing complete information to fertile women and their husbands’ by health provider as the key factor to improve the IVA test among fertile women.Keywords: Servical Cancer, women fertile age, visual inspection with acetic acid (IVA)